Exploring past research to move forward: a scoping review of aims, outcomes, and recommendations in parental mental illness qualitative research - Piché, Geneviève; Davidson, Gavin; Dunkley-Smith, Addy; Grant, Anne; Yates, Scott; Maybery, Darryl (Frontiers in Public Health, 2024)
Introduction As parental mental illness is a global public health concern, rigorous qualitative research is central to understanding families' experiences, needs and outcomes to inform optimal service provision in adult mental health and children's social services. Methods The current review identified, appraised and synthesized international qualitative research exploring Families and Parent Mental Illness (FaPMI) research to determine the focus, findings and outcomes and to summarize the recommendations made about the direction of future research. Findings are classified according to outcomes for children, parents, and families. Results While some children experienced positive outcomes from a parent's illness, most faced impacts on their social-emotional wellbeing, school performance, increased caregiving responsibilities, strained parent relationships, and lack of understanding about parental mental illness. Some family members endured abuse and struggled to adapt to an ill parent's unpredictable needs, with reluctance to discuss the situation. Parents found parenting challenging yet viewed having children as a protective factor. Future research should gather diverse perspectives, explore within-family factors and social environments, develop and test interventions, and address methodological issues like sampling. Discussion This review highlights the centrality of qualitative data in comprehensively understanding and evaluating outcomes of parental mental illness on families and provides clear recommendations regarding future research.